PENERAPAN TATA KELOLA KEUANGAN DAN MANAJEMEN YANG BAIK UNTUK MENINGKATKAN KINERJA UMKM HIMPUNAN PENGUSAHA NAHDLIYIN KABUPATEN BANYUMAS - Muksin, Abdullah; Marhalinda, Marhalinda; Suratman, Adji; Nursina, Nursina; Erianto, Dwi; Nugroho, M. Iman; Indriati, Lely (Universitas Mataram, 2024)
Micro, small and medium business actors who are members of the Nahdliyin Entrepreneurs Association (HPN) Banyumas Regency, Central Java were formed in April 2023 in Purwokerto Banyumas. Most of them still manage their business in a simple way. The priority problem faced by MSME actors is the capacity of MSME actors who are not yet able to manage their business, are not yet able to manage their business finances and are not yet optimal in marketing their products/services and are not yet able to create promotions with digital marketing. To improve the quality and capability of MSME actors in overcoming the priority problems they face. To increase the capacity of business actors who are able to prepare financial reports, digital marketing on social media and publish them in journals. The approach method used is training, guidance/consultation, mentoring, and supervision. Apart from that, determining procedures and solution steps in solving problems involving experts in the fields of business management, finance and entrepreneurship who are experienced in effective, efficient and competitive business management. The results of this PkM activity are, firstly, business actors can improve the quality and capability in managing their business. Second, being able to change your mindset, attitude and successful behavior and commitment so that you can manage your business effectively and efficiently. Third, business actors have been able to prepare budgets and financial reports according to PSAK ETAP standards. Fourthly, businesses have been able to advertise their products/services using digital marketing on social media, their own websites/bloqs. The quality of business actors has increased, they are able to manage their business finances using PSAK ETAP standards and are able to advertise their products/services using digital marketing.